The Effect of Self-Efficacy and Perception of Teacher Profession on Teaching Interest: Study on Bachelor Students of Office Administration Education - Annur, Eka Wati; Trisnawati, Novi (Universitas Negeri Surabaya, 2023)
This study aims to investigate the impact of self-efficacy and perceptions of the teaching profession on students' interest in pursuing a career as teachers within the Office Administration Education Study Program at Universitas Negeri Surabaya. This study was explanatory research using an associative quantitative approach. The population consisted of 52 respondents from the 2019 office administration education students, with a saturated sample. The data were analyzed using multiple linear regression, which had been pre-tested for classical assumptions with the assistance of the SPSS program. Based on the research results: (1) There is a positive correlation between self-efficacy and interest in becoming a teacher among students of the Office Administration Education Study Program at Universitas Negeri Surabaya. (2) There is a positive correlation between perceptions of the teaching profession and interest in pursuing a teaching career among students of the Office Administration Education Study Program at Universitas Negeri Surabaya. (3) There is a positive correlation between self-efficacy, perceptions of the teaching profession, and interest in in becoming a teacher among students of the Office Administration Education Study Program at Universitas Negeri Surabaya.